PENGARUH KECERDASAN EMOSIONAL DAN KESIAPAN BELAJAR TERHADAP MOTIVASI MENGERJAKAN TUGAS RUMAH SISWA KELAS X IPS MATA PELAJARAN EKONOMI DI SMAN 3 KOTA JAMBI - Mildawati Mildawati; Benar Sembiring (SJEE (Scientific Journals of Economic Education), 2020)
This study aims to determine the description and effect of learning readiness on the motivation to do homework for class X IPS in economic subjects at SMAN 3 Jambi City. (4) The effect of emotional intelligence and learning readiness on the motivation to do homework for class X IPS on economic subjects at SMAN 3 Jambi City. The results showed that (1) the description of emotional intelligence was in a fairly good category. Meanwhile, learning readiness is in the fairly good category at SMAN 3 Jambi City, (2) There is a significant influence between emotional intelligence on the motivation to do homework for class X IPS on economic subjects at SMAN 3 Jambi City. This is indicated by the value of tcount> ttable, which is 3.322> 1.659, (3) There is a significant influence between learning readiness on the motivation to do homework for students of class X IPS in economic subjects at SMAN 3 Jambi City. This is indicated by the value of tcount> ttable, namely 9.189> 1.659, and (4) There is a significant influence between emotional intelligence and learning readiness on the motivation to do homework for class X IPS in economic subjects at SMAN 3 Jambi City. This is indicated by the value of Fcount > Ftable, which is 42.274> 3.04.